2017
DOI: 10.1177/1533034617737923
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155 Promotes Uveal Melanoma Cell Proliferation and Invasion by Regulating NDFIP1 Expression

Abstract: MicroRNAs refer to small RNA molecules that destroy the messenger RNA by binding on them inhibiting the production of protein. However, the role of miR-155 in uveal melanoma metastasis remains largely unknown. In this study, we found that miR-155 was upregulated in both uveal melanoma cells and tissues. Transfection of miR-155 mimic into uveal melanoma cells led to an increase in cell growth and invasion; in contrast, inhibition of miR-155 resulted in opposite effects. Also, we identified Nedd4-family interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 33 publications
(35 reference statements)
2
43
0
4
Order By: Relevance
“…More and more evidence shows that miRNAs are dysregulated in various tumors, including melanoma. For instance, Peng et al (8) showed that miR-155 promotes uveal melanoma cell proliferation and invasion by regulating NDFIP1 expression. Liu et al (9) reported that miRNA-675 inhibits cell proliferation and invasion in melanoma by directly targeting metadherin.…”
Section: Introductionmentioning
confidence: 99%
“…More and more evidence shows that miRNAs are dysregulated in various tumors, including melanoma. For instance, Peng et al (8) showed that miR-155 promotes uveal melanoma cell proliferation and invasion by regulating NDFIP1 expression. Liu et al (9) reported that miRNA-675 inhibits cell proliferation and invasion in melanoma by directly targeting metadherin.…”
Section: Introductionmentioning
confidence: 99%
“…A relatively high levels of miR-155 was detected in B16F10-released exosomes compared with exosomes extracted from B16 cells. Previous studies indicated that overexpression of miR-155 can promote melanoma cell proliferation and invasion [ 37 ]. However, the effects of overexpression of miR-155 on melanoma angiogenesis have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Other oncogenic miRNAs include miR-155 [85], miR-20a [86], and miR-216a-5p that targets the hexokinase 2 (HK 2 ) gene involved in cell metabolism [87]. Interestingly, two oncogenic miRNAs have been shown to target PTEN in UM, namely miR-454 [88] and miR-367 [89].…”
Section: Mirna As Oncogenes In Ummentioning
confidence: 99%